Analisis Stakeholder dalam Pengembangan Wisata Alam Kea-Kea Mangolo di Kabupaten Kolaka - Sabaruddin, Abdul; Maulid, Maulid; Fait, Taslim; Maharani, Maharani (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Stakeholder involvement in tourism development is important in overcoming the limited resources of each actor. Kea-Kea natural tourist attraction in Mangolo Village, Latambaga Sub-district is one of the tourist attractions whose development involves various stakeholders. The purpose of this research is to identify stakeholders and the role of stakeholders involved and the development of Kea-Kea natural attractions. The method used in the research is descriptive qualitative. The results of the study found that the actors involved in the development of tourism objects consisted of the Kolaka Regency Tourism Office and the Natural Resources Conservation Centre (BKSDA) of Southeast Sulawesi Province which were key stakeholders. Then the tourism awareness group (Pokdarwis), companies (business sector), and the community. Pokdarwis is a primary stakeholder while companies and the community are secondary stakeholders. The role of each stakeholder is very strategic in the development of tourism objects. The government and BKSDA play a role in preparing road infrastructure, marketing (promotion), and preserving the nature of tourist attractions. The business sector is involved in providing facilities and infrastructure services. Pokdarwis play a role in maintaining cleanliness, maintaining and repairing supporting facilities for tourist attraction locations, and collecting retribution. However, the contribution of stakeholders in the development of tourism objects has not been maximized due to budget constraints, and lack of stakeholder awareness of the importance of tourism development.